Mother’s Knowledge and Dietary Patterns with Incidence of Stunting in Toddlers During New Normal - Dwi Syaputri Yanti; Sumardiyono Sumardiyono; Kusnandar Kusnandar (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Stunting is a developmental disorder characterized by inadequate height for age and chronic malnutrition resulting from a protracted food shortage. Stunting can be caused by a mother's lack of nutrition knowledge and her inability to get both quality and quantity of meals. This study aimed to explore the relationship between mothers' knowledge and dietary pattern with the incidence of stunting in toddlers aged 24-59 months during a new normal era in Solok Regency. This observational cross-sectional study was done in the working area of the Paninggahan, Batu Bajanjang, and Alahan Panjang Health Centers, Solok Regency, with 110 participants aged 24-59 months using Multistage Random Sampling. A questionnaire containing the characteristics of mothers and toddlers, mothers' knowledge, FFQ and IDDS forms were applied for data collecting. The data were then analyzed using the Chi-Square test. 60.9% of children aged 24-59 months were found to be stunted, according to the study. The Chi-Square test showed a relationship between the mother's knowledge and the incidence of toddler stunting (p = 0.024 and OR = 2.0). In addition, there is a substantial relationship between dietary patterns and the incidence of stunting in toddlers (p = 0.000 and OR=7.9). Abstrak: Stunting adalah gangguan perkembangan yang ditandai dengan tinggi badan yang tidak memadai untuk usia dan kekurangan gizi kronis akibat kekurangan makanan yang berkepanjangan. Stunting dapat disebabkan oleh kurangnya pengetahuan ibu tentang gizi dan ketidakmampuan ibu dalam mendapatkan makanan baik kualitas maupun kuantitas. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan ibu dan pola konsumsi dengan kejadian stunting pada balita usia 24-59 bulan pada masa adaptasi kebiasaan baru di Kabupaten Solok. Penelitian ini merupakan penelitian observasional dengan desain cross-sectional yang dilakukan di wilayah kerja Puskesmas Paninggahan, Batu Bajanjang, dan Alahan Panjang, Kabupaten Solok, dengan jumlah partisipan 110 orang berusia 24-59 bulan dengan menggunakan Multistage Random Sampling. Kuesioner yang berisi karakteristik ibu dan balita, pengetahuan ibu, formulir FFQ dan IDDS digunakan untuk pengumpulan data. Data kemudian dianalisis menggunakan uji Chi-Square. 60,9% anak usia 24-59 bulan ditemukan mengalami stunting, menurut penelitian tersebut. Uji Chi-Square menunjukkan bahwa ada hubungan antara pendidikan ibu dengan kejadian stunting pada balita (p = 0,024 dan OR = 2,0). Selain itu, terdapat hubungan yang bermakna antara pola konsumsi dengan kejadian kejadian stunting pada balita (p = 0,000 dan OR=7,9).